Pembelajaran Makhārij Al-Ḥurūf di Desa Rongdurin Kecamatan Tanah Merah Bangkalan - Islamiyah (PT. ALHAFI BERKAH INDONESIA, 2023)
A student, child and teenager, especially in Rongdurin Tanah Merah village, must have the ability to read the Koran rhetorically. One way is by studying Makhārij al-Ḥurūf. Because by studying and developing this knowledge, they can understand the most basic things about the hijaiyah letters. So that it can lead them to have the ability to read the Koran well. The formulation of the problem that will be raised in this activity is: